2017
DOI: 10.1177/000313481708300603
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Cystadenoma and Cystadenocarcinoma of the Gallbladder: A Clinical Review

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Only a few case reports have been reported primarily in the gallbladder. The first case was described by Bishop in 1901, in a 40-year-old woman with a large cystic lesion in the gallbladder (6). Authors reported only 10 cases of MCN in England between 1977 and 2017 (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few case reports have been reported primarily in the gallbladder. The first case was described by Bishop in 1901, in a 40-year-old woman with a large cystic lesion in the gallbladder (6). Authors reported only 10 cases of MCN in England between 1977 and 2017 (5).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known as benign lesions, there are studies reporting the association of the malignancy and MCN as well. It is reported that MCNs have a potential risk for progression to invasive carcinoma with a rate of 30% (6).…”
Section: Discussionmentioning
confidence: 99%